Biomaterials and Scaffold Design Strategies for Regenerative Endodontic Therapy - Raddall, Gavin; Mello, Isabel; Leung, Brendan M. (Frontiers in Bioengineering and Biotechnology, 2019)
Challenges with traditional endodontic treatment for immature permanent teeth exhibiting pulp necrosis have prompted interest in tissue engineering approaches to regenerate the pulp-dentin complex and allow root development to continue. These procedures are known as regenerative endodontic therapy (RET). A fundamental component of the regenerative endodontic process is the presence of a scaffold for stem cells from the apical papilla to adhere to, multiply and differentiate. The aim of this review is to provide an overview of the biomaterial scaffolds that have been investigated to support stem cells from the apical papilla in regenerative endodontic therapy and to identify potential biomaterials for future research. An electronic search was conducted using Pubmed and Novanet databases for published studies on biomaterial scaffolds for regenerative endodontic therapies, as well as promising biomaterial candidates for future research. The investigated scaffolds were organized in host-derived, naturally-derived and synthetic material categories. It was found that the biomaterial scaffolds investigated to date possess both desirable characteristics and issues that limit their clinical applications. Future research investigating the scaffolds presented in this article may, ultimately, point to a protocol for a consistent, clinically-successful regenerative endodontic therapy.